2007
DOI: 10.1021/bi700855j
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Initiation of Structural Characterization of Human Peripheral Myelin Protein 22, an Integral Membrane Protein Linked to Peripheral Neuropathies

Abstract: Gene duplications, deletions, and point mutations in peripheral myelin protein 22 (PMP22) are linked to several inherited peripheral neuropathies. However, the structural and biochemical properties of this very hydrophobic putative tetraspan integral membrane protein have received little attention, in part because of difficulties in obtaining milligram quantities of wild type and disease-linked mutant forms of the protein. In this study a fusion protein was constructed consisting of a fragment of lambda repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 102 publications
3
39
0
1
Order By: Relevance
“…A large body of literature supports the basic assumption of the model: For example, proteolysis of membrane proteins resulted in fragments containing entire TM sequences (Huang et al 1981), and chemically or recombinantly synthesized TM peptides spontaneously assembled thereby rescuing receptor activity (Kahn and Engelman 1992;Ridge et al 1995;Martin et al 1999;Wrubel et al 1994). Finally, peptides corresponding to the N and C terminus (Harmar 2001;O'Hara et al 1993), loop domains (Bennett et al 2004;Katragadda et al 2001a, b;Yeagle et al 2000) and transmembrane domains (Katragadda et al 2001a, b;Cohen et al 2008;Zheng et al 2006;Musial-Siwek et al 2008;Tian et al 2007;Lau et al 2008;Mobley et al 2007;Neumoin et al 2007) from GPCRs have been found to fold to distinct secondary structures which in certain cases resembled the structures of the corresponding regions of the intact receptor.…”
Section: Introductionmentioning
confidence: 83%
“…A large body of literature supports the basic assumption of the model: For example, proteolysis of membrane proteins resulted in fragments containing entire TM sequences (Huang et al 1981), and chemically or recombinantly synthesized TM peptides spontaneously assembled thereby rescuing receptor activity (Kahn and Engelman 1992;Ridge et al 1995;Martin et al 1999;Wrubel et al 1994). Finally, peptides corresponding to the N and C terminus (Harmar 2001;O'Hara et al 1993), loop domains (Bennett et al 2004;Katragadda et al 2001a, b;Yeagle et al 2000) and transmembrane domains (Katragadda et al 2001a, b;Cohen et al 2008;Zheng et al 2006;Musial-Siwek et al 2008;Tian et al 2007;Lau et al 2008;Mobley et al 2007;Neumoin et al 2007) from GPCRs have been found to fold to distinct secondary structures which in certain cases resembled the structures of the corresponding regions of the intact receptor.…”
Section: Introductionmentioning
confidence: 83%
“…If the hydrophilic surface areas of membrane proteins are too small to contribute sufficiently to polar-polar protein interactions, it will be difficult to obtain high-quality protein crystals. These problems may be solved by using large hydrophilic fusion partners to enlarge the hydrophilic portion of membrane proteins [20,21]. [6,7], alkaline phosphatase (Pho) [6,8,9], b-lactamase [9,10], chloramphenicol acetyltransferase (CAT) [10] Fluorescent protein tag Topology identification, displaying protein interactions…”
Section: Structural Investigations Of Membrane Proteinsmentioning
confidence: 99%
“…His tag [19][20][21][22], MBP [23], GST [24], Strep tag [25] Protein tag Expression partner, protein stabilization Large size Ubiquitin [19], cytochrome b562 [26], Protein Z [27], thioredoxin [28], Bcl-XL [29] Peptide tag Detecting proteins, topology identification, displaying protein interactions;…”
Section: Structural Investigations Of Membrane Proteinsmentioning
confidence: 99%
See 2 more Smart Citations